IDENTIFIKASI AKTIFIVITAS EKONOMI DAN NILAI EKONOMI SPASIAL DAS CILIWUNG - Nur Aini; Tridoyo Kusumastanto; Luky Adrianto; Agus Sadelie (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
The ecological, social and economic functions of the Ciliwung watershed are essentially to meet human needs, from primary to tertiary. The fulfillment of human needs occasionally contributes to the reduction of watershed ecological functions that result in flooding in Jakarta and declining ecological functions in the Jakarta Bay. Therefore, the study of the identification of economic activity and economic value spatially along the Ciliwung watershed needs to be done so as not to err in the management of the watershed in the future. This research uses survey method. Sampling using multi-stage sampling method. Spatial analysis of land use is done by using GIS by Arc / View method, economic value analysis is done with use value and non-use value. The use value approach uses a value-added production approach that is GDP of gross production of each sector of economy, non-use value using CVM approach by calculating WTP value. Percentage of Ciliwung Watershed cover: Forest 46.87 percent (Primary Forest 9.25 percent, Secondary Forest 25.25 percent, Plantation Forest 12.07 percent), Shrubs 0.62 percent, Plantation 1.06 percent, Dry Land Agriculture 9.68 percent, Rice Field 1.44 percent, Settlement 40.09 percent. Economic activity of The Downstream Ciliwung Watershed is dominated by the secondary sector (manufacturing, electricity, gas, water and construction). Economic activity of The Middle and Upstream Ciliwung Watershed is dominated by primary sector (Food crops, horticultural crops, plantation crops, Veterinary, Mining). The use value of Upper Ciliwung Watershed is Rp. 13.1 trillion, Middle Rp53.1 trillion and Downstream Rp. 1,117.6 trillion. Non-use value for the existence of The Upstream Ciliwung Watershed of Rp. 0.055 trillion, Rp. 0.235 trillion of The Middlel and Downstream Rp. 0.657 trillion per year. The economic value of Upstream Ciliwung Watershed is Rp. 13.12 trillion, Midle Rp5.545 trillion and Downstream is Rp. 1,118.31 trillion.